The impact of endometrial thickness change after progesterone administration on pregnancy outcome in patients transferred with single frozen-thawed blastocyst - Zhiqin Bu; Xinhong Yang; Lin Song; Beijia Kang; Yingpu Sun (BMC, 2019)
Abstract Background The aim of this study was to explore the impact of endometrial thickness change after progesterone administration on pregnancy outcome in patients transferred with single frozen-thawed blastocyst. Methods This observational cohort study included a total of 3091 patients undergoing their first frozen-thawed embryo transfer (FET) cycles between April 2015 to March 2019. Endometrial thickness was measured by trans-vaginal ultrasound twice for each patient: on day of progesterone administration, and on day of embryo transfer. The change of endometrial thickness was recorded. Results Regardless of endometrial preparation protocol (estrogen-progesterone/natural cycle), female age, body mass index (BMI), and infertility diagnosis were comparable between patients with an increasing endometrium on day of embryo transfer and those without. However, clinical pregnancy rate increases with increasing ratio of endometrial thickness. Compared with patients with Non-increase endometrium, those with an increasing endometrium on day of embryo transfer resulted in significantly higher clinical pregnancy rate (56.21% vs 47.13%, P = 0.00 in estrogen-progesterone cycle; 55.15% vs 49.55%, P = 0.00 in natural cycle). Conclusions In most patients, endometrial thickness on day of embryo transfer (after progesterone administration) increased or kept being stable compared with that on day of progesterone administration. An increased endometrium after progesterone administration was associated with better pregnancy outcome.